2016
DOI: 10.11648/j.js.20160402.18
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Transurethral Enucleation Resection of the Prostate for Symptomatic Benign Prostatic Hyperplasia

Abstract: Abstract:Transurethral enucleation resection of the prostate is safe and feasible for the treatment of symptomatic benign prostatic hyperplasia (BPH). However, long-term results of this treatment in patients with BPH have not been reported. To assess the efficacy and safety of this procedure, this study retrospectively evaluated long-term outcomes in 1400 consecutive patients who underwent transurethral enucleation resection of the prostate for BPH between 2008 and 2014. Patients were followed up at 1, 3, 6, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…In this study, the levels of CRP, IL-8 and IL-6 increased significantly after the first day of the operation and reached the peak at the third day and it decreased slowly afterwards. This results are similar to the relevant researches [8]. These results indicated that both TUERP and TURP can induce stress response.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the levels of CRP, IL-8 and IL-6 increased significantly after the first day of the operation and reached the peak at the third day and it decreased slowly afterwards. This results are similar to the relevant researches [8]. These results indicated that both TUERP and TURP can induce stress response.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, an ingenious minimally invasive endoscopic technology known as transurethral enucleation and resection of prostate (TUERP) has emerged for BPH treatment [5]. Compared to the conventional TURP technique, the TUERP bears clear advantages of better security, less blood loss and surgery time, and more complete glands-cutting [6][7][8].…”
Section: Introductionmentioning
confidence: 99%